Resistance to beta-lactam antibiotics and quinolones in Escherichia coli isolated from broilers - Carvajal B., Edna (2021)
The aim of this study was to determine the antimicrobial resistance of 176 Escherichia coli strains isolated from broiler chicken organs. The strains were challenged with beta-lactam, quinolones and fluoroquinolones, observing resistance to beta-lactam antibiotics (97.7%) and quinolones (86.7%). The results showed that 71.6% of the isolates phenotypically expressed the production of extended spectrum beta-lactamases (ESLB). By PCR, resistance genes for beta-lactams blaTEM, blaSHV, blaCTX-M1 and Amp-C and resistance genes for quinolones qnrA, qnrB, qnrS were determined. The genes Amp-C (74%), blaCTX-M (65%), blaSHV (65%), blaTEM (50%), qnrB (86.4%) and qnrS (11.9%) were found. The qnrA gene was not evident in the samples analysed. The results obtained revealed a large percentage of resistance to the studied antibiotics and the presence of resistance genes in isolates from poultry for human consumption, which constitutes a risk for Public Health.